2012
DOI: 10.1007/s11002-011-9158-x
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ evaluation of allocation policies for scarce health care services: Vested interest activation trumps spatial and temporal distance

Abstract: The allocation of scarce health care service resources often requires tradeoffs between individual and collective outcomes (e.g., when some individuals benefit more strongly from a given policy than others). Based on construal level theory, one would expect that consumers cognitively represent the individual and collective outcomes of an allocation policy at different levels of abstraction and that they evaluate allocation policies more positively when there is congruency between the cognitive representation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…The result of the between-subject effects of regulatory focus and graphics-text ratio on attitude toward the ads and behavior were statistically significant. Our results were consistent with previous research that reported that individuals with promotion focus preferred a high construal level, which indicates that they preferred abstract advertisements, and vice versa [ 23 , 37 ]. However, we determined that the interaction effects of regulatory focus and the graphics-text ratio were both directional and statistically significant when the manipulation was promotion focus.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The result of the between-subject effects of regulatory focus and graphics-text ratio on attitude toward the ads and behavior were statistically significant. Our results were consistent with previous research that reported that individuals with promotion focus preferred a high construal level, which indicates that they preferred abstract advertisements, and vice versa [ 23 , 37 ]. However, we determined that the interaction effects of regulatory focus and the graphics-text ratio were both directional and statistically significant when the manipulation was promotion focus.…”
Section: Resultssupporting
confidence: 92%
“…We investigated the interaction effect of temporal distance and the graphics-text ratio and found that the difference of behavior and attitude toward ads was bigger when the temporal distance was set as “in one year” than “in one month”. We surmised that this lack of significance could have occurred because the average age of participants in this study was approximately 27 years, which is too young to have sufficient knowledge regarding colorectal cancer, whereas the participants in previous studies were approximately 40 years or older [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 92%
“…Neural connections in the brain are arranged accordingly, with more abstract renderings located ''at higher points in the cortical hierarchy'' , p. 1204. Therefore, when psychological distance and construal level are congruent (close and low; far and high), cognitive processing is more fluent (Benning, Breugelmans, & Dellaert, 2012;Kim, Rao, & Lee, 2009) than when they are incongruent (close and high; far and low). This fluency has been illustrated through studies using implicit association tests; congruent pairings (close and low; far and high) were matched faster than incongruent ones (close and high; far and low; Bar-anan et al, 2006).…”
Section: Construal Levelmentioning
confidence: 98%
“…Armed with this knowledge, experienced buyers should construe that prices will decline over time such that lower prices are typically worth the search whether the event is coming sooner or later. Benning, Breugelmans, and Dellaert (2012) find that recent experience overruled temporal distance effects when considering health-care services. Kyung, Menon, and Trope (2014) show that those more experienced and knowledgeable more easily retrieve judgments, and this fluency or salience moderates temporal distance effects.…”
Section: Studymentioning
confidence: 88%